Current Trends in Wildlife Research - Mateo, Rafael; Arroyo, Beatriz; Garcia, Jesus T. (Wildlife Research Monographs, 2016)
This book, the first in the "Wildlife Research Monograph" series, defines "wildlife research" in a variety of contexts and reviews recent research trends. The authors present the current developments they have identified using bibliometric analyses of the most common, relevant and emerging topics in wildlife research over the last three decades. Diverse aspects of wildlife research are discussed, including wildlife demography, infections spread between wildlife, livestock and humans, habitat requirements and management, as well as the effects of renewable energy and pollutants on wildlife. Furthermore the authors explore topics like advances in the study of species distribution, invasive species, use of molecular markers in wildlife studies and the sustainability of wildlife exploitation and conservation conflicts. The book offers a comprehensive overview of advances in wildlife research in the last decades.